Publishers and the Public: Governmental Support in Europe - Smith, Kelvin (Javnost-The Public, 2004)
The aim of this paper is to explore some of the issues around why and how governments in Europe support the book. It looks at financial support for the creators, producers, promoters, and readers of printed books, and, while it touches on actions by European institutions, the focus is on national and regional activities. The objective is to try and identify different models of support for publishing and the book, and to compare some underlying cultural attitudes and policy objectives of different schemes. Actions in several countries are used to illustrate the different types of support provided, but there is particular reference to the French and British situations, where a variety of support schemes are operated by different branches of central government and by regional authorities.